Aplikasi Pengukuran Kualitas Sistem Informasi Cyber Campus Universitas Dinamika Dengan Metode Importance Performance Analysis Dan Webqual 4.0 - Catur Rochmat Hartanto; Jusak Jusak; M.J Dewiyani Sunarto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Dinamika University is one of the universities in Surabaya that focuses on informatics, design and business which is located on Jl. Raya Kedung Baruk No.98, Kedung Baruk, Kec. Rungkut, Surabaya City, East Java 60298. The university has 3 faculties and 8 departments, namely the Faculty of Technology and Information Technology. To assist the academic field in managing data and information there is an application for the Cyber Campus Information System or SiCyCa which is an academic information system. SiCyCa at Dinamika University contains several features such as academic, finance, library, E-Resource, PPKP, PPTA, Community, Questionnaire and Public Relations publications. . Based on the results of the questionnaire 60% of respondents from 43 respondents stated that SiCyCa has features that can be easily understood and display up to date information, in addition there are 40% of respondents from 43 respondents stated that respondents still have difficulties in communicating, so the University must continue to try as much as possible improve and improve SiCyCa services, especially in improving the ease of communication services. By using Importance Performance Analysis can identify the strengths and weaknesses of the variables used by the user in determining the choice of two criteria. The first criterion indicates the level of importance and the second criterion indicates the level of performance. By using IPA, you can find out which services are still lacking, which must be improved and which services must be maintained. The test results show that the IPA application is able to process data with a 100% success rate